PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN AGRO WISATA KEBUN TEH DI KABUPATEN SOLOK PROVINSI SUMATERA BARAT (JURNAL SPASIAL, 2016)
The tea gardens in the region Kayu Aro, Solok regency, West Sumatra, provides a beautiful panorama and the cool air and it has the potential to be developed it is done by empowering the community, The aim of this study was to determine how pemberdayakan community in the development of agro-tourism tea gardens in the district Solok of West Sumatra province, community empowerment is done by (1) the development of conservation-based, ie the pattern of community development while maintaining the authenticity of agro-ecosystems by seeking the preservation of natural resources environment, history, culture, and recreation. How to community development can be done in stages namely, done before the area became the object of agrotourism and after being selected as the object of agrotourism, (2) the development of agro-based tourism community, intended pattern of community development that puts an agro-tourism as the empowerment of farming communities to be able to obtain value-added both in terms of agricultural products as of tourist visits and a double effect on the absorption of agricultural produce by tourism enterprises and developers by specifying area / agro tourism by the government as an area / region development and inventory of strengths agro-tourism and the synergies between the community, the role of tourism agencies and agricultural institutions in the development of agro-tourism so that it can improve the aesthetic value and natural beauty.